Can self-leadership enhance the impact of motivation on entrepreneurial performance? - Fitri, Desi; Dwita, Vidyarini (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: The research is to investigate how self-leadership mediates the impact of motivation on entrepreneurial performance.Methodology: The study uses a quantitative descriptive approach with Structural Equation Modeling (SEM) through Smart-PLS to evaluate the effects of self-leadership, and motivation on the entrepreneurial performance of 125 entrepreneurs at one of the traditional markets in west Jakarta. Data were collected using a saturated sample technique, with questionnaires distributed to all entrepreneurs to obtain information. The analysis was conducted to assess the relationships among the variables and their influence on entrepreneurial performance.Finding: The empirical research findings indicate that self-leadership significantly mediates the impact of motivation on entrepreneurial performance.Conclusion: This study provides a unique framework for entrepreneurship to develop evidence-based practices that foster more productive and supportive entrepreneurs. It suggests that self-leadership is crucial for translating entrepreneurial motivation into effective actions and outcomes. The study contributes to the existing body of knowledge on human resource management in entrepreneurship by offering a framework that links motivational and self-leadership to enhance entrepreneurial performance.